Effect Of Superheated Steam (Shs) Pre-Treatment On Quality Of Fish Oil From Catfish (C/Arias Batrachus) - Veeriah, Harivaindaran (2015)
Superheated steam (SHS), a dry steam with temperature higher than boiling point that operates without the presence of oxygen is used to pre-treat catfish, Clarius batrachus, before being subsequently pressed via hydraulic press to obtain fish oil. Fish were first cleaned and reduced in size before being treated with SHS at 150°C, 200°C, 250°C, for 10, 15, 20 min for each temperature. Fish are then transferred into a mould, pressed using a hydraulic press and the resulting aliquot is centrifuged and oil is collected. Quality of the resulting fish oil is studied in terms of yield, colour, oxidation, thermal analysis and fatty acid composition. Yield of the catfish oil showed higher values when heated with higher temperatures of SHS, the highest being the 250°C, 20 minutes pre-treatment (8.91 gram/gram fish, significantly different at p> 0.05) which was incidentally lower than solvent extraction and this fact has been proven in past literature. Colour analysis showed tendency towards a darker yellow colour as treatment time and temperature increased. In terms free fatty acids (FFA) values, solvent extracted raw catfish oil had the highest and most significant value (2.56% oleic acid) and this reflected in high acid value beyond that of acceptable edible oil standard. However, peroxide values were mostly insignificantly different. The extent of oxidative damage was obvious in the p-anisidine values whereby at 250°C, 20 minutes pre-treatment, there was a sharp rise to 12.05 which, although significantly different, was still within edible oil standard.